2015
DOI: 10.1016/j.jsat.2014.09.002
|View full text |Cite
|
Sign up to set email alerts
|

A randomized trial of computerized vs. in-person brief intervention for illicit drug use in primary care: Outcomes through 12months

Abstract: This study examined outcomes through 12 months from a randomized trial comparing computerized brief intervention (CBI) vs. in-person brief intervention (IBI) delivered by behavioral health counselors for adult community health center patients with moderate-level drug misuse (N= 360). Data were collected at baseline, 3-, 6-, and 12-month follow-up, and included the Alcohol, Smoking, and Substance Involvement Screening Test (ASSIST) and laboratory analysis of hair samples. Repeated measures analyses examined dif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
17
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 34 publications
(22 citation statements)
references
References 36 publications
2
17
0
1
Order By: Relevance
“…Platforms for delivering addiction interventions via technology are diverse and multiplying rapidly. These include electronic screening and brief intervention (eSBIs)(Carey, Scott-Sheldon, Elliott, Bolles, & Carey, 2009; Copeland & Martin, 2004; Fachini, Aliane, Martinez, & Furtado, 2012; Gryczynski et al, 2015; Ondersma, Svikis, & Schuster, 2007); web-based multi-module programs and smartphone apps, with and without clinician involvement (Bickel, Marsch, Buchhalter, & Badger, 2008; Gustafson et al, 2014; Suffoletto et al, 2015) treatment delivered ‘live’ via Skype, telephone, or instant messaging (McKay, Lynch, Shepard, & Pettinati, 2005; McKay et al, 2004; McKay et al, 2011; McKay et al, 2010); monitoring via interactive voice response (IVR) and Ecological Momentary Assessment (EMA) and Ecological Momentary Treatment (EMT) platforms (Moore et al, 2013; Morgenstern, Kuerbis, & Muench, 2014) and several more (Muench, 2014). Overall, results from meta-analyses of such interventions are promising (Boumparis, Karyotaki, Schaub, Cuijpers, & Riper, in press; Carey et al, 2009; Riper et al, 2014; Rooke, Thorsteinsson, Karpin, Copeland, & Allsop, 2010; Tait, Spijkerman, & Riper, 2013), but methodological quality of studies within this young field is variable and often weak (Kiluk, Sugarman, et al, 2011).…”
Section: The Promise Of Technologymentioning
confidence: 99%
“…Platforms for delivering addiction interventions via technology are diverse and multiplying rapidly. These include electronic screening and brief intervention (eSBIs)(Carey, Scott-Sheldon, Elliott, Bolles, & Carey, 2009; Copeland & Martin, 2004; Fachini, Aliane, Martinez, & Furtado, 2012; Gryczynski et al, 2015; Ondersma, Svikis, & Schuster, 2007); web-based multi-module programs and smartphone apps, with and without clinician involvement (Bickel, Marsch, Buchhalter, & Badger, 2008; Gustafson et al, 2014; Suffoletto et al, 2015) treatment delivered ‘live’ via Skype, telephone, or instant messaging (McKay, Lynch, Shepard, & Pettinati, 2005; McKay et al, 2004; McKay et al, 2011; McKay et al, 2010); monitoring via interactive voice response (IVR) and Ecological Momentary Assessment (EMA) and Ecological Momentary Treatment (EMT) platforms (Moore et al, 2013; Morgenstern, Kuerbis, & Muench, 2014) and several more (Muench, 2014). Overall, results from meta-analyses of such interventions are promising (Boumparis, Karyotaki, Schaub, Cuijpers, & Riper, in press; Carey et al, 2009; Riper et al, 2014; Rooke, Thorsteinsson, Karpin, Copeland, & Allsop, 2010; Tait, Spijkerman, & Riper, 2013), but methodological quality of studies within this young field is variable and often weak (Kiluk, Sugarman, et al, 2011).…”
Section: The Promise Of Technologymentioning
confidence: 99%
“…The methodology and results of the trial have been described in detail elsewhere (Gryczynski et al, in press; Schwartz et al, 2014). Briefly, 360 adult patients with moderate-risk illicit drug misuse as defined by the Alcohol, Smoking, and Substance Involvement Screening Test (ASSIST) (Humeniuk et al, 2008) were randomly assigned on a 1:1 basis to receive an interactive computerized brief intervention (CBI) or an in-person brief intervention (IBI) delivered by an experienced, Masters-level behavioral health counselor.…”
Section: Methodsmentioning
confidence: 99%
“…The study found no significant differences between IBI and CBI on the primary outcomes of global ASSIST drug risk scores or drug-positive hair test results, while CBI outperformed IBI on several substance-specific drug risk scores examined as secondary outcomes. Analyses to date have examined the results of hair drug testing and self-reported ASSIST scores at a 3-month endpoint (Schwartz et al, 2014), and in terms of differential change through 12-months of follow-up (Gryczynski et al, in press). In summary, these analyses found no overall reductions, or between-condition differences in drug hair test results.…”
Section: Methodsmentioning
confidence: 99%
“…However few studies in the US or Mexico provide reliable estimates of the prevalence of drug use in primary care settings required to implement this strategy (Gelberg et al, 2015; Gryczynski et al, 2014; Lebrun-Harris, Tomoyasu, & Ngo-Metzger, 2014; Lee, Delbanco, Wu, & Gourevitch, 2011; Madras et al, 2009; McNeely et al, 2014a; Roy-Byrne et al, 2014; Saitz et al, 2014; Smith, Schmidt, Allensworth-Davies, & Saitz, 2010). Some information exists regarding the prevalence of substance use along the border for the general household population and emergency room patients, (Borges et al, 2009; Borges et al, 2015; Borges et al, 2011; Cherpitel et al, 2015; Guerrero et al, 2014), SUD specialty treatment centers (Sánchez-Huesca, Arellanez-Hernández, Pérez-Islas, & Rodríguez-Kuri, 2006), or among high risk populations (Chittoor et al, 2013; McDougal et al, 2013; Pitpitan et al, 2013; Servin et al, 2015).…”
Section: Introductionmentioning
confidence: 99%